Ethnobotany of Food Plants in The Malay Community in Ratu Sepudak Village, Galing District, Sambas Regency - Renianda; Rafdinal; Siti Ifadatin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The Malay people in Ratu Sepudak village use some kind of plant foods. The Malay culture of Ratu Sepudak Village is closely related to the use of plants as food. The purpose of this study was to determine the species of plants, plants parts, utilization categories and processing methods of food plants as well as to determine the value of citation frequency and informant agreement factor (FKI). This study was conducted from August to October 2022 in Ratu Sepudak Village, Galing District, Sambas recency. The method used in this study is purposive sampling and semi-structured interviews of 30 respondens. Quantitative analysis of this study using citation frequncy and informant agreement factor(FKI). Based on the research results food plants were obtained 72 species and 39 families. The most species found are Arecaceae, Poaceae, and Zingiberaceae, which are 6,94 % each. The most widely used part as food is fruit, which is 51,76%. Planst that are used as food ingredients are the most widely inclued in the category of utilization as vegetables as many as 29 types. The highest value of citation frequency of this study reaches 100%. Utilization category as a staple food and food coloring has the highest value of the informant agreement factor (FKI) is 1.